2009
DOI: 10.1159/000227814
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy and Safety of Amitriptyline in Patients with Cystic Fibrosis

Abstract: Amitriptyline, a blocker of acid sphingomyelinase and acid ceramidase, significantly reduces Pseudomonas aeruginosa lung infection in cystic fibrosis (CF) mice with concurrent increase of survival. Our aim was to establish whether amitriptyline is safe and effective in the treatment of CF patients. In a randomised, double-blinded, placebo-controlled, cross-over pilot study, 4 adult CF patients received 37.5 mg of amitriptyline or placebo twice daily for 14 days. Subsequently in a phase II study 19 adult CF pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 16 publications
1
48
0
Order By: Relevance
“…Based on the results of our previous studies [15], we used the difference of relative FEV 1 predicted between cases and controls after treatment of 28 days as primary endpoint.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the results of our previous studies [15], we used the difference of relative FEV 1 predicted between cases and controls after treatment of 28 days as primary endpoint.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously assessed the therapeutic efficacy and safety of amitriptyline in a pilot study involving 4 CF patients treated with amitriptyline or placebo demonstrating a significant increase in lung function after 2 weeks of treatment with amitriptyline. We subsequently performed a phase IIa study for safety, proof-of-mechanism and dose-finding study involving 19 CF patients [15]. This study revealed that amitriptyline is safe in CF patients, since only mild adverse effects were observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that ceramide also plays a very critical role in cystic fibrosis and normalization of ceramide levels by blockers of the acid sphingomyelinase has been shown to prevent infection and inflammation in cystic fibrosis patients [42][43][44], we hypothesize that a therapy that combines normalization of ceramide levels with inhalation of glucosylceramide and/ or sphingosine [17,37] might be the most promising way preventing or treating existing bacterial infection in CF patients in the future. Since other drugs, like antibiotics, can also be applied via an inhalation therapy in CF [45], this way of application offers the benefits of a local administration with minimal adverse systemic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings highlight the role of ceramide among sphingolipids in the pulmonary demise typical of chronic obstructive pulmonary disease (COPD) and Cystic Fibrosis (CF) (Grassme 2013, Petrache 2013. Gulbins and coworkers demonstrated that ceramide accumulates in CF airways and that amytriptiline, an inhibitor of the ceramidereleasing enzyme acid sphingomyelinase, reduces lung inflammation and bacterial infection in mice and in patients (Teichgraber 2008, Riethmuller 2009). We recently demonstrated that de novo ceramide synthesis also sustains lung inflammation and infection in CF (Caretti 2014) by using a murine CF model and pulmonary Pseudomonas aeruginosa infection to measure and pharmacologically target ceramide synthesis.…”
mentioning
confidence: 99%